2005
DOI: 10.1128/jvi.79.3.1966-1969.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Inhibits the Replication Cycle of Severe Acute Respiratory Syndrome Coronavirus

Abstract: Nitric oxide (NO) is an important signaling molecule between cells which has been shown to have an inhibitory effect on some virus infections. The purpose of this study was to examine whether NO inhibits the replication cycle of the severe acute respiratory syndrome coronavirus (SARS CoV) in vitro. We found that an organic NO donor, S-nitroso-N-acetylpenicillamine, significantly inhibited the replication cycle of SARS CoV in a concentration-dependent manner. We also show here that NO inhibits viral protein and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
273
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(282 citation statements)
references
References 35 publications
5
273
0
4
Order By: Relevance
“…Several other studies also found that anti-3a antibodies were presented only in a subset of SARS patients [4,9,10,22]. In this study, we showed that rabbit polyclonal antibody targeting a 14 aa epitope (aa [15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the N-terminal ectodomain of 3a could neutralize the SARS-CoV replication in Vero E6 cells in the absence of the complement system. On the other hand, serum obtained from a rabbit immunized with the Cterminal cytoplasmic domain of 3a (aa 134-274) was not capable of neutralizing SARS-CoV even though it contains a higher amount of 3a-specific antibodies.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…Several other studies also found that anti-3a antibodies were presented only in a subset of SARS patients [4,9,10,22]. In this study, we showed that rabbit polyclonal antibody targeting a 14 aa epitope (aa [15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the N-terminal ectodomain of 3a could neutralize the SARS-CoV replication in Vero E6 cells in the absence of the complement system. On the other hand, serum obtained from a rabbit immunized with the Cterminal cytoplasmic domain of 3a (aa 134-274) was not capable of neutralizing SARS-CoV even though it contains a higher amount of 3a-specific antibodies.…”
Section: Resultsmentioning
confidence: 60%
“…All experiments were performed in duplicates and the average values with standard deviations are plotted. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] in the N-terminal ectodomain of the 3a protein during SARS-CoV infection also remains to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the beneficial effects persisted after termination of NO inhalation [135]. NO has been shown to inhibit the replication cycle of SARS-CoV in vitro [136].…”
Section: No (Nitric Oxide)mentioning
confidence: 97%
“…In vitro studies demonstrated that NO significantly interfers with the replication cycle of SARS CoV in a concentration-dependent manner and also inhibits viral protein and RNA synthesis [136,142]. When Chen and colleagues [143] treated a small cohort of 6 severely sick SARS patients in their intensive care unit with NO in addition to the ribavirin/steroid therapy, they observed improvement in oxygenation and decreased spread or density of lung infiltrates.…”
Section: Drugs Used In Sars Treatmentmentioning
confidence: 93%